Two new species of fanged frog from Southeastern Borneo, Indonesia (Amphibia: Anura: Dicroglossidae) - Gonggoli, Ade Damara; Shimada, Tomohiko; Matsui, Masafumi; Nishikawa, Kanto; Sidik, Irvan; Kadafi, Ahmad Muammar; Farajallah, Achmad; Hamidy, Amir (Zootaxa, 2025)
Two new species of dicroglossid frog of the Limnonectes kuhlii complex are described from southeastern Borneo, Indonesia. These new species were previously confused with L. kuhlii, whose type locality is Java, but recognized to represent genetically distinct lineages. Here, we describe them based on molecular and morphological characteristics. The two new species, Limnonectes maanyanorum sp. nov. and Limnonectes nusantara sp. nov., can be distinguished from named species of the Limnonectes kuhlii complex from Borneo, Java, Sumatra, and Peninsular Malaysia by significant genetic distances in partial sequences of the 16S rRNA gene and combinations of morphological characters. These descriptions are an initiation step in taxonomic work to encourage studies of the L. kuhlii complex in Kalimantan, Indonesia.